Community Economic Strengthening through a Circular System in the View of Sharia Maqashid - Tari Rizkya Fona; Reni Ria Armayani Hasibuan; Muhammad Ikhsan Harahap (International Journal of Economics Development Research (IJEDR), 2023)
This study explains the concept of strengthening the community's economy through a circular system in the view of maqashid sharia. In strengthening the circular economy, the people of Kel. Rengas Pulau Kec. Medan Marelan utilize organic waste that is reprocessed into circular economy products in the form of compost. The purpose of this study is to determine strategies in strengthening the community economy to develop a circular economy in accordance with the principles of sharia maqashid and analyze obstacles in strengthening the circular economy. This research uses qualitative methods using the NVivo application that supports searching for common words in data search frequency, displaying data analysis in the form of tables, graphs, tree structures and comparison tables based on data coding results. The results show that strengthening the circular economy requires ongoing responsibility by improving accessibility and infrastructure. The need for broader targets, assistance and training on proper waste management to the community. The obstacles that occur in strengthening the community's economy through the circular system are lack of education to the community, lack of public concern for the environment, lack of support from the government in helping provide capital assistance in the form of organic waste shredding machines, still lack of awareness from the public about the importance of sorting waste and the absence of specific regulations regarding the importance of not littering. Maqashid shari'ah at TPST 3R Mahkota Medan Marelan implicitly fulfills the basic elements of maqashid shari'ah. Aspects of competence, quality, moral ethics, trust, in the process of waste business governance, as an effort to hifzu addin (maintain religion), and hifzu al-nasb (maintain offspring). Second, knowledge, understanding and awareness of waste management as a resource, as an effort hifzu al-nafs (protecting the soul), hifzualaql (protecting the mind).